The Second Transmembrane Domain of the Human Type 1 Angiotensin II Receptor Participates in the Formation of the Ligand Binding Pocket and Undergoes Integral Pivoting Movement during the Process of Receptor Activation - Domazet, Ivana (American Society for Biochemistry and Molecular Biology, 2009)
The octapeptide hormone angiotensin II (AngII) exerts a wide variety of cardiovascular effects through the activation of the angiotensin II type-1 (AT(1)) receptor, which belongs to the G protein-coupled receptor superfamily. Like other G protein-coupled receptors, the AT(1) receptor possesses seven transmembrane domains that provide structural support for the formation of the ligand-binding pocket. In order to identify those residues in the second transmembrane domain (TMD2) that contribute to the formation of the binding pocket of the AT(1) receptor, we used the substituted cysteine accessibility method. All of the residues within the Leu-70 to Trp-94 region were mutated one at a time to a cysteine, and, after expression in COS-7 cells, the mutant receptors were treated with the sulfhydryl-specific alkylating agent methanethiosulfonate-ethylammonium (MTSEA). MTSEA reacts selectively with water-accessible, free sulfhydryl groups of endogenous or introduced point mutation cysteines. If a cysteine is found in the binding pocket, the covalent modification will affect the binding kinetics of the ligand. MTSEA substantially decreased the binding affinity of D74C-AT(1), L81C-AT(1), A85C-AT(1), T88C-AT(1), and A89C-AT(1) mutant receptors, which suggests that these residues orient themselves within the water-accessible binding pocket of the AT(1) receptor. Interestingly, this pattern of acquired MTSEA sensitivity was altered for TMD2 reporter cysteines engineered in a constitutively active N111G-AT(1) receptor background. Indeed, mutant D74C-N111G-AT(1) became insensitive to MTSEA, whereas mutant L81C-N111G-AT(1) lost some sensitivity and mutant V86C-N111G-AT(1) became sensitive to MTSEA. Our results suggest that constitutive activation of the AT(1) receptor causes TMD2 to pivot, bringing the top of TMD2 closer to the binding pocket and pushing the bottom of TMD2 away from the binding pocket.